Utilizing Body Languages to Create Effective Classroom Management - Rambe, Sokhira Linda Vinde (English Education : English Journal for Teaching and Learning, 2023)
The research investigated the use of teachers’ body languages in teaching English which focused on describing types of body language that teachers used and their significances in creating good classroom management. The kind of the research was descriptive qualitative in which the research used observation with note-taking and video-recording as data gathering techniques. Then, interview was also used to validate the data related to observation result. Then, an English teacher who teaches at SMP N 8 Padangsidimpuan was chosen as a research respondent. The steps of data analysis technique consisted of: (1) Reducing the data, (2) Presenting the data, and (3) Concluding the data. From the result of data analysis and discussion, there are five types of body language found in the research. They are facial expression, posture, gesture, touch, and eye contact. It was also found that body language must be used effectively and well to manage teacher’s teaching comfort and to monitor students’ learning activity like the use of postures and eye contact.